The Psychological Challenges of Emergency Medical Service Providers During Disasters: A Mini-Review February 2022 - Alghamdi, Abdullah Abdulaziz (Frontiers in Psychiatry, 2022)
The provision of emergency medical services (EMS) is an inherently stressful job. Depression, anxiety, and posttraumatic stress disorder (PTSD) are common psychological challenges affecting EMS providers. As disasters increase worldwide, the need for EMS also increases, as they are an essential part of any disaster management system. Studies have shown that EMS providers experience psychological challenges due to disaster response without receiving the needed psychological support. There is a scarcity of research focusing on EMS providers' psychological challenges in disaster times, especially in the Eastern world. This review highlights the psychological challenges faced by EMS providers in disaster times and discusses the amount of mental health care they receive. By emphasizing the need for mental health support, more research can be conducted to view EMS providers' perspectives on mental health needs before, during, and after disasters, and EMS policy makers can find programs to meet EMS providers' mental health needs, which might reflect positively on EMS and disaster management systems.